Pengaruh Site Quality terhadap Repurchase Intention (Studi Pada Konsumen Bukalapak.com di Indonesia) - Fitri Yanti, - (2021)
The purpose of this research is to study consumer perceptions of the ease of using the Bukalapak.com application. The survey was conducted on Bukalapak consumers in Indonesia with a population of 2,501,900 Facebook followers on Bukalapak.com. The results of the research using questionnaires reveal that research on site quality is quite good and can be applied by the Bukalapak.com site to attract consumers to repurchase intention. So that when consumers hear the Bukalapal.com site, consumers will not hesitate to make the purchase process through the Bukalapak.com site. Keywords: site quality, repurchase intention, customer Bukalapak.com.